Association between physical activity levels and functional recovery, quality of life, and psychological well-being in patients undergoing physiotherapy for musculoskeletal disorders: A cross-sectional study - Batool Abdulelah Alkhamis; Ravi Shankar Reddy; Mastour Saeed Alshahrani; Zuhair Al Salim; Faisal M. Alyazedi; Ahmed Mohamed Elshiwi; Ghada Mohamed Koura; Devika Rani Sangadala; Debjani Mukherjee; Saeed Y. Al Adal; Hussain Saleh H. Ghulam (PLoS ONE, 2026)
Physical activity is known to enhance functional recovery and quality of life (QoL) in individuals with musculoskeletal disorders; however, the extent to which varying levels of physical activity influence rehabilitation outcomes—and how demographic and clinical factors moderate these effects—remains inadequately understood. This cross-sectional study investigated the associations between physical activity levels and functional recovery, QoL, and psychological well-being among 286 adults undergoing physiotherapy at a tertiary care hospital in Abha, Saudi Arabia. Participants were classified into low, moderate, or high physical activity groups based on metabolic equivalent of task (MET) hours per week, using the culturally adapted Arabic version of the International Physical Activity Questionnaire – Short Form (IPAQ-SF). Outcome measures included the Patient-Specific Functional Scale (PSFS), the 36-Item Short Form Health Survey (SF-36), and the Hospital Anxiety and Depression Scale (HADS). Multiple linear regression analyses, adjusted for age, gender, socioeconomic status, and comorbidities, revealed that higher physical activity levels were significantly associated with greater functional recovery (β = 0.36, 95% CI: 0.06 to 0.66, p = 0.021), higher QoL (β = 0.42, 95% CI: 0.10 to 0.74, p = 0.011), and lower anxiety (r = –0.41, p = 0.013) and depression scores (r = –0.38, p = 0.022). Moderation analysis indicated that age and comorbidities negatively influenced the relationship between physical activity and recovery outcomes. The full model explained 68% of the variance in functional recovery (R² = 0.68, ΔR² = 0.16 with moderators, p = 0.023). These findings indicate that higher physical activity levels are associated with more favorable rehabilitation outcomes among individuals undergoing physiotherapy for musculoskeletal disorders; however, due to the cross-sectional design, causality cannot be inferred, and the generalizability of these associations requires further investigation.